Analisis Perceived Barrier yang Mempengaruhi Minat Wanita Pasangan Usia Subur (PUS) dalam Mengikuti Program KB di Wilayah Kerja Puskesmas Jati 1 - Wiwit Punagi Mukti; Aisyah lahdji; Nina Anggraeni Noviasari; Hema Dewi Anggraheny (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Perceived Barrier Analysis Affecting the Interest of Women of Reproductive Age  in Participating in the Family Planning Program in The Working Area of The Jati 1 Health Center. The number of women participated in the family planning program in the Jati 1 Health Center work area was 12% while the target was 80%. One component of the HBM that discusses obstacles to family planning is perceived barriers. The purpose of this study was to analyze perceived barriers that influence the interest of women in participating in the family planning program in the Jati 1 Health Center work area. This research method uses a qualitative analytical description.The study was conducted in the Jati 1 Health Center work area in 2022. The number of main informants in this study was 4 respondents and 4 triangulation informants. The sampling method was snowball sampling. The results showed that women's interest in participating in the family planning program related to perceived barriers was fear of the side effects of family planning and myths believed by the surrounding community made women not interested in participating in the family planning program.This study concludes that there is an influence between knowledge about family planning, number of children, and husband's support on the interest of women in participating in the family planning program in the work area of Jati 1 Health Center.